Students Competence To Determine The Uterine Fundal Height Between The Use Of The Silicone Phantoom And The Burtas Phantoom - Novianti, Lily; Komariah, Nurul (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Postpartum hemorrhage is the most common cause of maternal death. About 23-24% are caused by retained placenta. Suspicion of the presence of retained placenta can be identified by palpating the abdomen, to monitor contractions and uterine fundal height. Assessing uterine fundal height in postpartum women is one of the competency that must be achieved by Diploma III Midwifery graduates. This research was a cross sectional study with data collection techniques through observation to compare student’s competence to determine the uterine fundal height between the use of a silicone phantoom and a burtas phantoom. The research subjects were all 95 of 3rd semester students of the Diploma III Midwifery Study Program at the Health Polytechnic of Palembang. The research instruments were a silicone phantoom, a burtas phantoom and a checklist sheet. The research results showed that from the 95 students (100%) who used burtas phantoom to assess the uterine fundal height, 72 students (75.8%) were competen and 23 students (24.2%) were not competen to do the assesment. The p value was 0.001, it means that there was a difference in student’s competence in assessing uterine fundal height on the two phantooms. Students are more competen to asses uterine fundal height by using burtas phantoom than silicone phantoom. The OR value was 0.091. It means that using a silicone phantoom, the risk was 0.091x students not competen to assess the uterine fundal height compared to a burtas phantom Keywords: Burtas Phantoom, Student’s Competence